Insya’ Learning Based On Ta’bīrāt Asy-Syā’i’ah Using A Communicative Approach - Iklil Syaqifah; Nurhadi Nurhadi; Shofil Fikri; Muhammad Asyrofi Hasyim (Al-Wazan: Journal of Arabic Education, 2026)
Proficiency in Arabic writing remains a complex challenge for higher-education students, primarily due to an overemphasis on grammatical rules rather than communicative competence, which makes written works lack spontaneity and natural dynamics. To address this issue, this study aims to describe and analyze the implementation of insya’ (expressive writing) learning integrated with ta’bīrāt asy-syā’i’ah (popular idiomatic expressions) through a communicative approach at AIQ Nuris 2 Jember. This study employed a qualitative approach with a case study design. Data were collected via observation, interviews, and documentation involving language instructors and mahasantri, and then analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The findings reveal that the implementation is systematically executed across three structured phases: planning, execution, and assessment. Despite the limited availability of printed references for contemporary idioms, instructors effectively utilized digital platforms and authentic social media sources to provide relevant linguistic stimuli. The integration of ta’bīrāt asy-syā’i’ah   significantly enhanced the quality of students' writing, with highly positive responses reporting substantial improvements in the flexibility, expressiveness, and naturalness of their written Arabic. This study contributes valuable practical strategies and theoretical insights for developing functional and authentic Arabic writing instruction within Islamic boarding school (pesantren) environments.